(In)visibility of the Displaced Populations: the Blind-Spot Effect - Balinchenko, Svitlana (Sociologija. Mintis ir veiksmas, 2020)
In this paper, conflict-triggered internal displacement is reviewed through the visibility of migration-affected groups, as well as their access to decision-making. The blind-spot effect in the migration studies extends the cognitive and social implications of the systems theory, and engulfs both hypovisibility through anopticism and pseudoassimilation, and hypervisibility through panopticism and excessive control of the displaced citizens. In the context of the impact of IDP status on visibility assessment, I suggest supplementing the migration-studies’ concepts of “phlogiston” and “witch” with that of “ethanethiol”, thus starting a discussion on the role of the otherness marker in the migrantising of citizens. The case of protracted internal displacement in Ukraine due to the Russia-backed armed conflict serves as an illustration of the displaced populations’ visibility challenges and solutions.
Keywords: internal displacement; visibility; anopticism; panopticism; Ukraine